Photolithographic modification of polyethylene glycol silane monolayer for development of label-free dengue biosensor - Rosly, Nor Zida (2015)
Dengue disease becomes critical global health issue after millions were infected worldwide every year, which lead to fatality due to late detection. Hence, a new technique has been explored to improve the performance of the detection in term of time, price, sensitivity and selectivity. In order to develop the diagnostic devices, electron beam (e-beam) or ultra-violet (UV) lithography were used to fabricate smallsized patterns to provide surfaces with high sensitivity and selectivity to biomolecules. For this particular project, polyethylene glycol (PEG)-silane monolayer, which was the best-known antifouling polymer was used as a lithographic template due to its nonpolar, non-toxic and non-immunogenic properties of the surface. The monolayer formed was thoroughly characterized with contact angle, atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS). The AFM and contact angle data showed a uniform surface and hydrophilic properties of PEG-silane monolayer obtained which confirmed by the XPS. The e-beam and UV irradiations were subsequently performed, which generated the aldehyde functional groups. These offers conjugation sites for the immobilization of DNA dengue. Further studies were done to verify the presence of aldehyde functionality by testing with reducing agent and 2- amino-1,1,1-trifluoroethane (TFEA). The TFEA test showed an increased value of contact angle from 42° to approximately 74°, suggesting the hydrophobicity of surface that corresponds to the bonding of carbon atom to three fluorine atoms was formed. The reduction test studied the reduction aldehyde to alcohols which resulted in the decrease of contact angle values. The properties of gold nanoparticles (AuNPs) on particles sizes, shape, morphology and elemental composition were investigated which was utilized as a colorimetric probe for the determination dengue-DNA. For the DNA hybridization, target DNA was attached directly to probe DNA that had been immobilized on irradiated modified surfaces in which an amine-terminus (or Nterminus) from the DNA bound with aldehyde on modified surfaces. Gold enhancement process was introduced for naked eye detection after inducing electrostatic interaction between positively charged AuNPs and negatively charged target DNA to probe DNA. Control experiments were performed with mismatch DNA sequences to confirm the selectivity of the sensor. The effect of target DNA concentration was studied in the hybridization of DNA. The results obtained indicate an efficient and selective device have been successfully developed for label-free dengue detection.